Pure Bending of Homogenous Isotropic Elastic Curved Beam - Ecsedi, István; Baksa, Attila; Habbachi, Marwen (International Journal of Engineering and Management Sciences, 2023)
In this paper a detailed analysis is given for the pure bending problem of curved beams. The material of the curved beam is homogenous isotropic linearly elastic. The mantle of the curved beam is stress free and there is no body force on the curved beam. The plane of the curvature of the beam is the plane of symmetry for the whole beam. Paper gives the expressions of circumferential and radial normal stresses. A strength of material approach is used to derive the governing equations. A numerical example illustrates the application of the presented solutions.